The Status of Web 2.0 in Iran's LIS Education / Maryam Sarrafzadeh, Afsaneh Hazeri and Soheila Alavi - Sarrafzadeh, Maryam; Hazeri, Afsaneh; Alavi, Soheila (2011)
The present paper discusses results of a study which aimed to explore the knowledge and use of Web 2.0 technologies by LIS academics in Iran and to explore the challenges they face for using these technologies. More specifically, the study was to find answers to the following questions: 1. How do Iran's LIS educators rate their awareness of Web 2.0 tools? 2. How and in what ways Iran's LIS educators use Web 2.0 tools and services for academic purposes? 3. What are the problems that inhibit Iran's LIS educators from using Library 2.0 applications? The research method was explorative and empirical. Data was collected through a web-based survey questionnaire containing both open and close ended questions. The results show that LIS academics in Iran had good level of familiarity with some Web 2.0 tools such as blog, wiki, YouTube and Facebook. However, their familiarity with some other Web 2.0 tools such as RSS feeds, Twitter, Flickr, Delicious and podcast was limited. Blog, discussion groups, chat tools, file sharing tools, Wikis and SMS, video sharing tools and forum were used respectively by LIS academics in their teaching. Internet filtering was identified as the most inhibiting barrier to the use of Web 2.0 tools. Lack of access to high speed internet and lack of training were pointed as the other identified barriers. Authors suggest that to reap the benefits of Web 2.0, LIS academics need to find alternative non filtered Web 2.0 tools to employ in their teaching and research.